Separate variables to transform the equation to
[1 / (n*(1 - (n/k))] dn = r dt and then integrate both sides.
For the LHS we have
integral((k / (n*(k - n))) dn). Now note that k/(n*(k - n)) = (1/n) + (1/(k - n)),
so the integral becomes
integral[((1/n) + (1/(k - n))) dn] =
(ln(n) - ln(k - n)) + C = ln(n / (k - n)) + c.
The RHS integrates to just r*t + b, so after combining constants b - c = C we have
ln(n / (k - n)) = r*t + C. Now n(0) = k*ln(No / (k - No)) = C, so we now have
(ln(n / (k - n)) = r*t + k*ln(No / (k - No)) ----->
ln(No / (k - No)) - ln(n / (k - n))] = - r*t ----->
ln[No * (k - n) / ((k - No) * n)] = - r*t ----->
No * (k - n) / ((k - No) * n) = e^(-r*t) ---->
No*k - No*n = n*(k - No)*e^(-r*t) ---->
No*k = n*(No + (k - No)*e^(-r*t)) ----> n = No*k / (No + (k - No)*e^(-r*t)).
[1 / (n*(1 - (n/k))] dn = r dt and then integrate both sides.
For the LHS we have
integral((k / (n*(k - n))) dn). Now note that k/(n*(k - n)) = (1/n) + (1/(k - n)),
so the integral becomes
integral[((1/n) + (1/(k - n))) dn] =
(ln(n) - ln(k - n)) + C = ln(n / (k - n)) + c.
The RHS integrates to just r*t + b, so after combining constants b - c = C we have
ln(n / (k - n)) = r*t + C. Now n(0) = k*ln(No / (k - No)) = C, so we now have
(ln(n / (k - n)) = r*t + k*ln(No / (k - No)) ----->
ln(No / (k - No)) - ln(n / (k - n))] = - r*t ----->
ln[No * (k - n) / ((k - No) * n)] = - r*t ----->
No * (k - n) / ((k - No) * n) = e^(-r*t) ---->
No*k - No*n = n*(k - No)*e^(-r*t) ---->
No*k = n*(No + (k - No)*e^(-r*t)) ----> n = No*k / (No + (k - No)*e^(-r*t)).
-
Sorry, I messed up those two lines while I was editing my answer. they should read
"ln(n / (k - n)) = r*t + C. Now ln(No / (k - No)) = r*0 + C = C, so we now have
ln(n / (k - n) = r*t + ln(No / (k - No)) -----> " and then the rest of the solution
remains as it is. Good catch. :)
"ln(n / (k - n)) = r*t + C. Now ln(No / (k - No)) = r*0 + C = C, so we now have
ln(n / (k - n) = r*t + ln(No / (k - No)) -----> " and then the rest of the solution
remains as it is. Good catch. :)
Report Abuse